A randomized, placebo‐controlled trial to assess the efficacy and safety of sitagliptin in Japanese patients with type 2 diabetes and inadequate glycaemic control on ipragliflozin. Issue 6 (28th February 2021) - Seino, Yutaka; Kaku, Kohei; Kadowaki, Takashi; Okamoto, Taro; Sato, Asako; Shirakawa, Masayoshi; O'Neill, Edward A.; Engel, Samuel S.; Kaufman, Keith D.
Abstract: Aims: To investigate the efficacy, safety and tolerability of sitagliptin 50 mg once daily added to ipragliflozin 50 mg once daily monotherapy in Japanese patients with type 2 diabetes (T2D). Materials and Methods: Japanese patients with T2D and glycated haemoglobin (HbA1c) 7.0% to 10.0% while treated with ipragliflozin 50 mg once daily were randomized 1:1 to additional treatment with sitagliptin 50 mg once daily ( N = 70) or matching placebo ( N = 71) for 24 weeks. The primary efficacy endpoint was change in HbA1c at Week 24. Secondary efficacy endpoints were changes in 2‐hour post‐meal glucose (PMG), total PMG 0‐ to 2‐hour area under the curve (AUC0‐2h ), and fasting plasma glucose (FPG). Results: Baseline characteristics were similar in the two groups (mean age 55.5 years, mean baseline HbA1c 8.0%). After 24 weeks, the addition of sitagliptin provided significantly greater reduction in HbA1c compared to placebo (least squares [LS] mean difference −0.83% [95% confidence interval −1.05, −0.62]; P <0.001). Significant reductions were also observed in all secondary endpoints: LS mean differences from placebo in changes in 2‐hour PMG, total PMG AUC0‐2h, and FPG were −42.5 mg/dL, −67.0 mg·h/dL and −11.2 mg/dL, respectively (all P <0.001). The incidence of adverse events (AEs) overall and incidence of predefined AEs of clinical interest (symptomatic hypoglycaemia, urinary tract infection, genital infection, hypovolaemia and polyuria/pollakiuria) were similar in the two groups. Conclusions: In Japanese patients with T2D, sitagliptin 50 mg once daily added to ipragliflozin 50 mg once daily monotherapy provided significant improvement in glycaemic control and was generally well tolerated. ClinicalTrials.gov: NCT02577016.